A Numerical Fluid-Solid Coupling Model for the Dynamics of Ships in Atrocious Sea Conditions. Issue 2 (June 2015) - Chen, Xin; Zhou, XinCong; Zhang, Shesheng; Li, Dan
Adopting fluid dynamics theory and time-dependent solid dynamics theory of ship, the fluidsolid coupling dynamics numerical model is built. The linear fluid-solid coupling equation is derived from ship surface integral formula. The time-dependent hull displacement is calculated by solving the non-linear elastic equations. The results show that Green function has some interesting properties, and that the maximal displacement will appear when the wave-hull resonance number becomes an integer.